Selfconcept and self-control in students of secondary level of private institutions of Lima sur - León Pacheco, Yulian (2019)
Objetive: This research aimed to determine if there is a significant relationship between self-controland self-concept in students at the secondary level of private institutions in south Lima. Materials andMethods: Non-experimental cross-sectional and correlational design were used. Likewise, intentionalnon-probabilistic sampling was used between male and female students aged between 11 and 18years. Results: The results showed that 46.3% of participants had low levels of self-concept, and71.1% had self-control at medium and high levels. In addition, there is a moderate positive and highlysignificant relationship between the level of global self-concept and self-control (r =, 270, p <0.01).Accordingly. Conclusions: We conclude that self-concept is related to moderate and significant selfcontrol.